Influence of Leadership Style, Motivation, Work Environment and Compensation to The Performance of Office Officers Camat Rasanae West Bima City - Haerunnas Haerunnas (Jurnal Ilmiah Mandala Education (JIME), 2020)
The Office clerk of the West city of Bima has felt the best performance in carrying out its duties and expecting rewards alongside salaries or wages as an incentive to the achievements he has given. The purpose of this research is to know whether leadership style, motivation, work environment and compensation affect employee performance.This research was conducted in the office of West Surabaya's headquarters in Bima with a population of 130. The samples used were 70 respondents. Independent variables in the study are leadership style, motivation, work environment and compensation, while dependent variables are employee performance. Performance measurement is done using Likert scale. Data analysis is done by double linear regression model with back-Ward method applied SPSS Program version 14.00 for window.From standard estimate to variable leadership style (X1), motivation (X2), Work Environment (X3), compensation (X4) and employee performance (Y), it can be created structural equations as follows Y = 20,981 + 0.051 X1 + 0.215 X2 + 0.132 X3 + 0.067 X4 + ei. The results of the analysis showed that employees ' performance variables were influenced by leadership styles, motivations, working environments and simultaneous compensation or together by 85.30% while the remaining 14.70% were influenced by other factors beyond the model of this study.